ANALISIS PERTUMBUHAN EKONOMI DAN TINGKAT KETIMPANGAN PEMBANGUNAN DI PROVINSI NUSA TENGGARA BARAT - Suprianto Suprianto; Marisha Sutanty; Andipta Ahmad Zulkia (Jurnal Ekonomi & Bisnis, 2022)
This study aims to analyze economic growth and the level of development inequality in the Province of West Nusa Tenggara in 2017-2020. The analytical tools used in this study are the Williamson index and the Klassen typology. The Williamson Index is a coefficient of variance that measures the difference in the level of income per capita relative to a reference area, while the Klassen typology analysis is used to describe the pattern and structure of economic growth in each region. The results showed that in the Province of West Nusa Tenggara there has been a high distribution inequality. This is due to the migration of productive people who are skilled/educated to areas that have developed, because there they get higher wages/salaries. In addition, investment tends to apply in areas that have developed due to market factors, the profit is relatively large, as well as the risk of loss is relatively smaller, so it tends to result in the concentration of social and economic capital in areas that have developed due to greater demand. The structure of economic growth in the province of West Nusa Tenggara has different characteristics for each of the existing districts/cities.